Bioactive glass nanotube scaffold with well-ordered mesoporous structure for improved bioactivity and controlled drug delivery. Issue 9 (September 2019) - Xiao, Jian; Wan, Yizao; Yang, Zhiwei; Huang, Yuan; Yao, Fanglian; Luo, Honglin
Abstract: In this study, a novel mesoporous bioactive glass nanotube (MBGN) scaffold has been fabricated via template-assisted sol-gel method using bacterial cellulose (BC) as template and nonionic block copolymer (P123) as pore-directing agent. The scaffold was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier-transform infrared (FTIR) spectroscopy, and N2 adsorption-desorption analysis. Furthermore, simvastatin was used to evaluate the loading efficiency and release kinetics of the scaffold. The obtained scaffold displays nanofiber-like morphology, ordered mesopores on the tube walls, and interconnected three-dimensional (3D) network structure that completely replicates the BC template. In addition, it shows dual pore sizes (16.2 and 3.3 nm), large specific surface area (537.2 m 2  g −1 ) and pore volume (1.429 cm 3  g −1 ). More importantly, the scaffold possesses excellent apatite-forming ability and sustainable drug release as compared to the counterpart scaffold without mesopores. This unique scaffold can be considered a promising candidate for drug delivery and bone tissue regeneration.